2021
DOI: 10.3390/su13020798
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Preferences of Iranian Geotourists: Case Study of Shadows Canyon and Canyon of Jinns

Abstract: Compared to other parts of the country, the region of Central Iran still remains mainly outside of major tourism flows even though there are significant geosites with great value for geotourism development. Two of those sites, the Shadow Canyon and the Canyon of Jinns, have excellent qualities for the development of this form of tourism in the future. The goal of this research is to gain information about the preferences of Iranian geotourists and to determine the current state and geotourism potential of Shad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Furthermore, authors found that the understanding of a given area results in a better rating given to it by tourists. These findings are similar to ones from [18] which observed that Iranian geotourists deemed the rarity of a geosite and the number and quality of viewpoints as most important reasons for visit. The promotion of valuable geological sites should be part of bigger projects meant to develop tourism in poorly developed areas.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, authors found that the understanding of a given area results in a better rating given to it by tourists. These findings are similar to ones from [18] which observed that Iranian geotourists deemed the rarity of a geosite and the number and quality of viewpoints as most important reasons for visit. The promotion of valuable geological sites should be part of bigger projects meant to develop tourism in poorly developed areas.…”
Section: Introductionsupporting
confidence: 89%
“…Hypogene caves are found mainly in the Northwest, the Central and Easter zone, where they are associated with the igneous activity, and the Zagros zone. [18,33]).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This new methodology has its roots in previous assessment models and studies, all mainly related to resources such as geoheritage [4,[38][39][40][41][42], spas and hot springs [43] and cultural heheritage [44][45][46][47][48], and their use for tourism. These methods have been succesfully applied numerous times in the assessment of various geosites [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68], spas [43,[69][70][71], and sites of cultural heritage [44,47,48]. The majority of tourism related subindicators were derived from these existing models and been adapted in this study for saline soil assessment, while the subindicators Geomorphological attractiveness, Pedodiversity, Biodiversity, Endemic and relict plant species and Ambience were introduced by the authors of this paper, based on the opinion of experts.…”
Section: Methodsmentioning
confidence: 99%
“…Even though motivation and constraints have been widely studied in tourism, the existing literature directly related to motivation and constraints in a geotourism context is very limited. There are studies regarding the typology of geotourists and their preferences [51][52][53][54][55][56][57][58][59], but research on geotourism motivation and constraints still remains to be explored in a greater extent.…”
Section: Introductionmentioning
confidence: 99%